FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT DI INDONESIA - Ranita Ramadhani; Septyana Ananda Fatimah (Jurnal GeoEkonomi, 2022)
This study aims to examine the effect of time pressure, audit risk, materiality, and audit experience on premature audits. The data used in this study are primary data derived from respondents' answers to the questions in the questionnaire. This research was conducted on auditors who work in Public Accounting Firms (KAP) located throughout Indonesia. The results of the analysis show that time pressure, audit risk and auditor experience have a significant effect on premature audit, while materiality variable has no effect on premature audit.